Right To Be Forgotten Vis-À-Vis Hak Atas Informasi - Heribertus Untung Setyardi (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Abstract Right to be forgotten (RBF)is defined as a mechanism provided by electronic system providers to delete electronic information or electronic documents that are considered irrelevant in relation to a person. When looking at the meaning of RBF, it can be said that this is also closely related to information, because one of the things that is asked to be